Synthesis of Fe3C branches via a hexamethylenetetramine route. (April 2016) - Zhang, Peng; Bi, Lingling; Zhang, Daguang; Wang, Xiaobai; Wang, Wei; Lei, Xiang; Yang, Hua
Graphical abstract: Highlights: Fe3 C branches were prepared in a flexible method. As-synthesized Fe3 C branches perform a core–shell microstructure with a graphite shell. Excellent magnetism of Fe3 C branches has been obtained. Abstract: Fe3 C has been successfully prepared though a sol–gel process, performing good magnetic properties, whose saturated magnetization can be adjusted by the heating temperature. The introduction of hexamethylenetetramine (HMTA) improves the interference from Fe and ferrite, realizing a flexible and high-efficient route to iron carbide by tertiary amine. We believe the carbon-capsulated Fe3 C will be a potential candidate in magnetic materials.